Obtención de escopolamina del foripondio/brugmasia pers. y su relevancia en hechos delictivos para su uso en el laboratorio de química forense - Zamora Lojan, Freddy (2012)
Research is very important as it gives us a technique that is disables to do it in the lab to be very reliable and allows us to compare the effects of scopolamine in us that we will be cautions and know to defend this new criminal method.